Outer Retinopathies Associated with COVID-19 Infection: Case Reports and Review of Literature - Naima Zaheer; Mohammad O. Tallouzi; N. Ajith Kumar; Sreekanth Sreekantam (Case Reports in Ophthalmological Medicine)
Background. The coronavirus disease (COVID-19) is a highly contagious disease with profound health implications. It can affect any part of the body with variable severity. Various ophthalmic manifestations of coronavirus disease have been documented. Case Presentations. We reported three cases of outer retinopathies associated with COVID-19 infection. All three patients were young females. The first two patients presented within days of COVID-19 infection with complaints of black spots in the eyes. Multimodal retinal imaging showed lesions consistent with acute macular neuroretinopathy. Lesions were bilateral in the first patient and unilateral in the second one. Our third patient presented with blurred vision in one eye, 3 months after a suspected COVID-19 infection. Retinal imaging showed outer retinopathy. Our patients’ vision was good and maintained during the follow-up. All three were monitored on observation only, and symptoms and lesions improved with time. Conclusion. In conclusion, COVID-19-related thromboinflammatory response can result in localized vascular inflammation and hypoperfusion in any of the retinal capillary plexuses or choriocapillaris resulting in ischemia of the corresponding retinal or choroidal layers.